2000
DOI: 10.1016/s0082-0784(00)80546-9
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of hydroxyl radicals with trichloroethylene: Evidence for chlorine elimination channels at elevated temperatures

Abstract: Rate coefficients are reported for the gas-phase reaction of the hydroxyl radical (OH) with C 2 HCl 3 (k 1 ) over an extended temperature range at 740 ‫ע‬ 10 torr in a He bath gas. Rate measurements exhibited complex behavior with a slight negative temperature dependence at temperatures below 650 K and positive temperature dependence at higher temperatures (650-750 K). The three-parameter modified Arrhenius equation adequately describes all of the data and is given by (in units of cm 3 moleculeError limits are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…For example, the difference in the rate coefficients for the reaction of OH radicals with the stereoisomers of 1,2-dichloroethene is relatively small, ∼10 to 15%, , compared with the differences observed in the present study for the CF 3 CHCHCl stereoisomer reactions. There are limited studies available for chlorinated propenes, ,, but more detailed studies are available for the chloroethenes. , In general, the substitution of fluorine (or a CF 3 group in the present case) or chlorine atoms to the double bond in an unsaturated hydrocarbon decreases its overall reactivity with OH. The rate coefficients for reactions and measured in this work are substantially less than the typical range of rate coefficients observed for the OH radical addition reaction for unsaturated hydrocarbons, which are on the order of ∼10 –11 cm 3 molecule –1 s –1 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, the difference in the rate coefficients for the reaction of OH radicals with the stereoisomers of 1,2-dichloroethene is relatively small, ∼10 to 15%, , compared with the differences observed in the present study for the CF 3 CHCHCl stereoisomer reactions. There are limited studies available for chlorinated propenes, ,, but more detailed studies are available for the chloroethenes. , In general, the substitution of fluorine (or a CF 3 group in the present case) or chlorine atoms to the double bond in an unsaturated hydrocarbon decreases its overall reactivity with OH. The rate coefficients for reactions and measured in this work are substantially less than the typical range of rate coefficients observed for the OH radical addition reaction for unsaturated hydrocarbons, which are on the order of ∼10 –11 cm 3 molecule –1 s –1 .…”
Section: Resultsmentioning
confidence: 97%
“…The reported yield for the Cl elimination channel therefore represents a lower-limit because other Cl atom loss processes are expected under the conditions in the Sulbaek Andersen et al study; that is, reaction with the parent and reference compounds. The presence of a Cl atom elimination channel is not unprecedented because several studies have reported or discussed the mechanism for a Cl atom yield in the analogous OH + chloroethene reactions. , In these reaction systems the Cl atom yield was found to be greatest for OH addition to the chlorine-substituted carbon atom. For example, the Cl yield for the OH + 1,2-dichloroethene reaction is near unity, whereas the yield in the OH + 1,1-dichloroethene reaction is much less, <0.1 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical modeling indicated that the dominant source of OH decay in the absence of the substrate was reaction with HONO (k 298 ) 4.5 × 10 -12 cm 3 molecule -1 s -1 ). 16 A plot of k′ vs substrate concentration at selected temperatures is shown in Figure 2.…”
Section: Experimental Approach and Data Reductionmentioning
confidence: 99%
“…Spin-projected PMP4/6-311+G-(d,p) theory works well for the other chlorinated ethylenes as seen in this work and elsewhere. [10][11][12] Potential sources of error include deficiencies in the correlation treatment and basis set size, but implementation of sufficiently high levels of theory is nontrivial. Preliminary studies at the QCISD(T)-based G3(MP2) level yielded an even higher barrier of about 3 kcal mol -1 , so presumably, much more demanding correlation treatments and/ or basis sets are needed.…”
Section: J Phys Chem a Vol 105 No 32 2001mentioning
confidence: 99%